Surface plasmon resonance effects of silver nanoparticles in graphene-based dye-sensitized solar cells - Li, Xinxi; Yang, Wensheng; Deng, Jian; Lin, Yuanwei (Frontiers in Materials, 2023)
Localized surface plasmon resonance (LSPR) has been applied in photovoltaic devices to improve their photoelectric conversion efficiency. In this study, the mechanism of LSPR in dye-sensitized solar cells (DSSCs) was determined. Specifically, silver nanoparticles were formed by evaporating silver in electro-beam equipment and then annealing it in a tube furnace. The sizes of the nanoparticles varied with the changes in their thicknesses during evaporation and annealing. A DSSC-based graphene was designed to consist of different sizes of metal nanoparticles assembled on a cathode electrode. The photon electric performance of the DSSCs, which depended on Ag nanoparticles, was analyzed in detail, with a particular focus on nanoparticle size. Compared with the DSSC without Ag nanoparticles, the DSSC with LSPR exhibited excellent electric current density and incident photon-to-current efficiency (IPCE) performance due to the LSPR effect. The DSSC assembled with 10 nm-thick Ag film and annealed to form nanoparticles exhibited a high IPCE of 70.03%. The IPCE value of this DSSC was 45.15% higher than that of the pure graphene-based DSSC (31.62%). However, Ag nanoparticles increased to a certain degree and became aggregated and concatenated, thereby decreasing the LSPR effect on DSSCs. Therefore, LSPR plays an important role in the photon-electrical performance of DSSCs